2021
DOI: 10.1111/jnc.15458
|View full text |Cite
|
Sign up to set email alerts
|

Fluid metabolic pathways after subarachnoid hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating cerebrovascular disease with high mortality and morbidity. In recent years, a large number of studies have focused on the mechanism of early brain injury (EBI) and delayed cerebral ischemia (DCI), including vasospasm, neurotoxicity of hematoma and neuroinflammatory storm, after aSAH. Despite considerable efforts, no novel drugs have significantly improved the prognosis of patients in phase III clinical trials, indicating the need to further re‐examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 229 publications
0
17
0
Order By: Relevance
“… 2 , 3 The monolayer endothelial cells of the cerebral arterioles, also known as brain microvascular endothelial cells (BMECs), are vulnerable to injury due to the presence of anatomically weak vessel structures that lack elastic intima and smooth muscles in the media layer. 4 , 5 Studies have revealed that diffuse injury to the BMECs induced by cytotoxic metabolites of erythrocytes in the CSF is an important pathological change after SAH. 6 As a trigger of “secondary brain injury” after SAH, diffuse BMEC injury is related to dysfunction of the BBB, an increased risk of cerebral vasospasm and delayed cerebral ischemia, which lead to poor prognosis in patients with SAH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 The monolayer endothelial cells of the cerebral arterioles, also known as brain microvascular endothelial cells (BMECs), are vulnerable to injury due to the presence of anatomically weak vessel structures that lack elastic intima and smooth muscles in the media layer. 4 , 5 Studies have revealed that diffuse injury to the BMECs induced by cytotoxic metabolites of erythrocytes in the CSF is an important pathological change after SAH. 6 As a trigger of “secondary brain injury” after SAH, diffuse BMEC injury is related to dysfunction of the BBB, an increased risk of cerebral vasospasm and delayed cerebral ischemia, which lead to poor prognosis in patients with SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Generally caused by intracranial aneurysm (IA) rupture, SAH is characterized by diffuse distribution of blood in the subarachnoid space, in which the cerebral microvascular bed is immersed in cerebrospinal fluid (CSF) containing cytotoxic metabolites of blood components 2,3 . The monolayer endothelial cells of the cerebral arterioles, also known as brain microvascular endothelial cells (BMECs), are vulnerable to injury due to the presence of anatomically weak vessel structures that lack elastic intima and smooth muscles in the media layer 4,5 . Studies have revealed that diffuse injury to the BMECs induced by cytotoxic metabolites of erythrocytes in the CSF is an important pathological change after SAH 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For patients with brain atrophy, we believe due to decreased adhesion connecting lesions to surrounding tissues and the surrounding lower intracranial pressure (ICP) (25), aneurysms might be more prone to rupture with a sudden fluctuation of blood pressure. In addition, the enlarged subarachnoid space and lower ICP outside the lesion make formation of a localized hematoma difficult, which could be an important factor related to the hemostatic effect in the acute phase after SAH (26). Moreover, due to brain atrophy, bleeding is more likely to spread diffusely in the subarachnoid space on the surface of brain tissues, which could be a major contributor to the high Fisher grade after aneurysm rupture in this age group (27).…”
Section: Discussionmentioning
confidence: 99%
“…As we previously proposed and reviewed, 19 there are three steps of microcirculation disturbance after SAH: microcirculation compensation, decompensation and irreversible phases. After microvasospasms in the compensation period, platelet aggregation 20 and leukocyte plugging 21 in capillaries cause microcirculatory dysfunction in the decompensation phase.…”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 99%
“…16 In addition, free iron (Fe 3+ ) released from haemolytic red blood cells is also involved in arteriolar and capillary microvasospasms after SAH in mice, 17 while iron deposits in the cortex have been reported to be associated with cognitive outcomes in SAH patients. 18 As we previously proposed and reviewed, 19 there are three steps of microcirculation disturbance after SAH: microcirculation compensation, decompensation and irreversible phases. After microvasospasms in the compensation period, platelet aggregation 20 and leukocyte plugging 21 in capillaries cause microcirculatory dysfunction in the decompensation phase.…”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 99%